Avrupa-Akdeniz Ortaklığı: Barcelona Süreci - Ömer Kurtbağ (Ankara Avrupa Çalışmaları Dergisi)
This article attempts to analyze the en ı ergence and development ofEC/EU's Mediterranean Policy initiatives, the motives behind these initiatives,their degrees of success and failure and, finally, their future in context of theMiddle East developments and especially Arab-Israeli conflict and PeaceProcess. After the overview of early relations between the EC andMediterranean Countries in 1960s, the Global Mediterranean Policy which isdesigned in early 1970s and the Renovated Mediterranean Policy which islaunched in late 1980s, it focuses on the overall assessment of the BarcelonaProcess, which is by far the most relevant of existing Euro-Med Initiatives, withits potential and difficulties in light of the results of the ministerial meetingsfrom Malta in 1997 to Valencia in 2002.